Labor Market Effects of High School Science Majors in a High STEM Economy - Tarun Jain; Abhiroop Mukhopadhyay; Nishith Prakash; Raghav Rakesh (Institute of Labor Economics (IZA), 2018)
This paper explores the association between studying science at the higher secondary stage and labor market earnings using nationally representative data on high school subject choices and adult outcomes for urban males in India. Results show that those who studied science in high school have 22% greater earnings than those who studied business and humanities, even after controlling for several measures of ability. These higher earnings among science students are further enhanced if the students also have some fluency in English. Moreover, greater earnings are observed among individuals with social and parental support for translating science skills into higher earnings. Science education is also associated with more years of education, likelihood of completing a professional degree, and among low ability students, working in public sector positions.
Keywords: 23; I26; J24; 330; high-school majors; labor markets; science; STEM; India